Sociological Aspects in the Determination of Islamic Law - Ismail Keri; Achmad Musyahid; Kurniati Kurniati (Al-Bayyinah, 2022)
Islamic law, as inherent in legalizing a problem faced by society, is an interesting discussion in the reflection of religious law in society. How not, the problems faced by the community continue to grow and are always global, as a large current that must find a solution. The dialogue between the sociological aspect and the establishment of Islamic law is a discourse that continues to get attention and must get factual answers as a result of reformulation of Islamic law towards a better direction. This study is a conceptual study or literature review, which examines data from Islamic law books, books and journals that have relevance. The result of the research shows that, the constructive relation of Islamic law between the sociological aspect and its stipulation is something that cannot be separated. The determination of Islamic law, always considering the sociological aspects of society, shows that the law is for human beings, so it is not surprising that Islamic law is flexible and measurable. The implication that is born in the sociological aspect is the establishment of a sweet and elastic Islamic law determination while still paying attention to its normative and historical aspects.